(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2023)
Resistance of the minority other and their coexistence within the dominant group is one of the oldest striking issues in the social and political ideologies of several Arab countries. It is viewed as a major aspect upon which society’s safety, social stability and well being are based. For example the group of Imazighen[1] in Morocco has been struggling to be as linguistically and culturally recognized as Arab people; they have been resisting to live as an unimportant minority in the eye of the dominant group or as another whose culture and language do not conform to the relevant ongoing evolution of the society. Accordingly, this paper purports to investigate the notion of minority (Imazighen) resistance and coexistence in the dominant group (Arabs) under the tenets of ethnographic research approach. The study takes place in Ain Taoujdate[2] city as the area of investigation, and it opts for the interview and the story telling task as two instruments for qualitative data collection. To that end, two main patterns of result are yielded; concerning coexistence among groups, participants reveal that at the surface all groups or subgroups coexist with each other and no conflicts emerge in this area; however, formal and firm ties characterize their coexistence in the sense that close relationships are reserved merely for members of one’s own group. As far as the notion of minority resistance is concerned, interviewees ‘stories display that Imazighen‘s centuries old struggle for recognition results in the officialization of the Amazigh language and its symbolic implementation in the school curricular; yet, such processes are mere words on paper and Imazighen are still underrepresented in most social spheres in the Moroccan society. [1] The indigenous people of Morocco are Imazighen or the Berbers, as different civilizations have referred to them. [2] Morocco is divided into 12 regions; Ain Taoujdate belongs to the third region of Fes-Meknes in the province of Elhajeb in the middle Atlas of Morocco. It lies on an area of 446,550 km2 with a population of 216 388 inhabitants, 92 540 are males while females constitute 123 848 from the whole population. Like most of the cities in the province of Elhajeb, this area is known by its agricultural activities which make basic groundwork upon which the economy of the city relies, (Morocco’s population census, 2014).